The neoconservative revolution : Jewish intellectuals and the shaping of public policy - Friedman, Murray, 1926-2005 (Cambridge University Press, 2005)
His book suggests that Jews and Jewish intellectuals have played a considerable role in the development of modern American conservatism. The focus is on the rise of a group of Jewish intellectuals and activists known as neoconservatives who began to impact on American public policy during the Cold War and in the lead up to and invasion of Iraq. It presents a portrait of the life and work of the original small group of neoconservatives including Irving Kristol, Norman Podhoretz, and Sidney Hook. This group has grown into a new generation who operate as columnists in conservative think-tanks like The Heritage and The American Enterprise Institute, in education, and in government including such figures as Paul Wolfowitz, Richard Perle and Elliot Abrams. The book suggests the neo cons have been so significant in reshaping modern American conservatism and public policy that they constitute a neoconservative revolution.